Differentiating between testicular toxicity and sexual immaturity in ortho-phthalaldehyde inhalation toxicity studies in rats and mice - Catlin, Natasha R. (Toxicol Pathol, 2018)
Early deaths of young or juvenile animals (before sexual maturation is achieved) in routine regulatory safety studies present pathologists and toxicologists with the challenge of interpreting findings in the male reproductive tract. Additionally, the advent of toxicity testing regulations have resulted in a growing need for the use of juvenile animals in toxicology studies. Here we present the reproductive toxicity findings from a 13-week inhalation toxicity study with ortho- phthalaldehyde (OPA) in male rats and mice as a case example for working through this challenging task. In this study with OPA, survival was significantly reduced in the two highest exposure concentrations of OPA tested. Early deaths and histopathological lesions in the testes and epididymides were generally also limited to these two highest exposure groups. Therefore, there was concern that peripubertal morphological features could be a confounding factor for the histopathological evaluation of exposure-related testicular and epididymal findings. Although it can be difficult to differentiate exposure-related effects from the normal morphological features defining peripubertal changes in the testes and epididymides in animals that die early in a toxicity study, the use of age-matched controls in this case study with OPA provided a reference and aided in the differentiation of these effects.